Chromosome-Level Genome Assembly of Anthidium xuezhongi Niu & Zhu, 2020 (Hymenoptera: Apoidea: Megachilidae: Anthidiini). (12th February 2022) - Zhang, Dan; Jin, Jianfeng; Niu, Zeqing; Zhang, Feng; Orr, Michael C; Zhou, Qingsong; Luo, Arong; Zhu, Chaodong
Abstract: Anthidiini, a large bee tribe characterized by light-colored maculations, represents nearly 1, 000 pollinator species, but no genomes are yet available for this tribe. Here, we report a chromosome-level genome assembly of Anthidium xuezhongi collected from the Tibetan Plateau. Using PacBio long reads and Hi-C data, we assembled a genome of 189.14 Mb with 99.94% of the assembly located in 16 chromosomes. Our assembly contains 23 scaffolds, with the scaffold N50 length of 12.53 Mb, and BUSCO completeness of 98.70% ( n = 1, 367). We masked 25.98 Mb (13.74%) of the assembly as repetitive elements, identified 385 noncoding RNAs, and predicted 10, 820 protein-coding genes (99.20% BUSCO completeness). Gene family evolution analyses identified 9, 251 gene families, of which 31 gene families experienced rapid evolution. Interspecific chromosomal variation among A. xuezhongi, Bombus terrestris, and Apis mellifera showed strong chromosomal syntenic relationships. This high-quality genome assembly is a valuable resource for evolutionary and comparative genomic analyses of bees.